Implementation of Teacher Development Policy in Indonesia - Garina Siskawati; Leni Ramadani; Cahaya Rahma; Izandy Izandy; Mulyadi Mulyadi (Universitas Muhammadiyah Enrekang, 2024)
Policy was created to replace industry. This technology concept aims so that human life is not eroded by technology and can solve some problems that occur today, especially in the field of education. This study aims to analyze the implementation of societyon teacher development policies in Indonesia and this research uses library research methods . Some of the problems that occur today are lack of teacher development and lack of teacher knowledge on the use of learning media technology. The policies prepared by the government to overcome these problems already exist, but in terms of implementation there are still shortcomings especially technological developments are now increasingly rapid, therefore the need for adjustments between society to teacher development policies and the use of learning media today.